Continuing education for the chiropractic profession: a cross-sectional study analyzing potential barriers to future chiropractic academic and research development - Shannon Schueren; Dean L. Smith; Christopher A. Malaya; Jeffrey A. King; Nathan D. Schilaty (Chiropractic & Manual Therapies)
Abstract Background Continuing education (CE) for chiropractors is mandated by state licensing boards to ensure ongoing learning and to maintain professional excellence. While incorporating research into CE programs is crucial for practitioners to remain dynamic and evidence-based, conducting research and academic pursuits is necessary for further development of the profession. We hypothesized that fewer U.S. states would provide CE credit for the completion of research or higher-education teaching activities within the chiropractic profession compared to other health professions. Methods Internet searches of publicly available state board websites for each profession was undertaken with a cross-sectional study design between 12/19/2024 and 03/01/2025. Data extraction focused on whether CE was granted for research (publication and/or peer review) as well as academic pursuits (higher education and/or CE instruction). Descriptive statistics determined the frequency of states allowing CE while Fisher’s Exact test and one-way ANOVA was performed to compare states granting CE credits for research and teaching as well as comparisons among the professions. Results Only 16 US states allow DCs to claim research activities for CE credit while 50% allow teaching for CE credit. This is significantly lower (p < 0.001) than ATs, DOs, and MDs where teaching and research activities are accepted for CE credit in all states. Conclusions Precluding research and higher-education teaching opportunities for CE presents a potential barrier to chiropractic academic and research development at present and in the future.